Shiloh : a biblical city in tradition and history - Schley, Donald G. (Journal for the study of the Old Testament. Supplement series, 1989)
This work is the first comprehensive treatment of the biblical traditions pertaining to the Israelite sanctuary at Shiloh. A survey of previous research puts the current discussion of Shiloh into historical context and exposes the real issues behind the often bitter debate over Shiloh's supposed destruction during the Philistine wars and its traditional status as the first 'central' shrine.